Pengaruh Model Pencegahan Stunting Berbasis Pemberdayaan Kader dalam Upaya Peningkatan Pengetahuan dan Sikap Ibu - Yurissetiowati, Yurissetiowati; Tabelak, Tirza Vivianri Isabela; Yulianti, Hasri (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Background: Stunting is failure to grow and develop in children under 5 years of age and is caused by chronic malnutrition which is characterized by below normal body length or height. In 2021 in Indonesia, the prevalence of stunting is around 7.9%. This figure includes East Nusa Tenggara Province which has a stunting rate of 26.3%. In the Kupang Regency area, stunting cases have a prevalence of 25.5%. In Olenasi village, it was recorded that out of a total of 240 toddlers, 36 toddlers were in the short category and 9 toddlers were in the very short category with a prevalence rate of 18.8%. The aim of this research activity is to increase the knowledge and attitudes of mothers of toddlers and prevent stunting in babies by empowering cadres in Oelnasi village. This research is a type of quantitative research with a Quasi Experimental research design using a pre-test group research design and a post-test design. The population of this study were Posyandu implementing cadres and mothers with toddlers who lived in Oelnasi Village, Kupang Regency. The number of samples in this study was 30 cadres and 60 mothers with toddlers. The independent variable in this research is the empowerment of toddler posyandu cadres, and the dependent variable is the knowledge and attitudes of toddler mothers towards stunting. The research instrument used in this study was a questionnaire regarding mothers' knowledge and attitudes towards stunting. The knowledge and attitudes of mothers of toddlers were measured before and after being given counseling by cadres. Based on the SPSS test on mothers' knowledge and attitudes using the Wilcoxon test, the result was p = 0.001 or a significance level of p < 0.05, which means there is a difference between the mother's level of knowledge and attitudes before and after empowering cadres using the counseling method. The conclusion in this research is that there is an influence of cadre empowerment in efforts to increase the knowledge and attitudes of mothers of toddlers in Oelnasi Village.